2004
DOI: 10.1161/01.cir.0000139337.56084.30
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Changes in Stented Human Coronary Arteries

Abstract: Background-Restenosis after stenting occurs secondary to the accumulation of smooth muscle cells (SMCs) and extracellular matrix (ECM), with the ECM accounting for Ͼ50% of the neointimal volume. The composition of the in-stent ECM has not been well characterized in humans. Methods and Results-Postmortem human coronary arteries (nϭ45) containing stents underwent histological assessment of neointimal proteoglycans, hyaluronan, collagen (types I and III), SMCs, and CD44 (a cell surface receptor for hyaluronan). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
121
0
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(138 citation statements)
references
References 48 publications
7
121
0
7
Order By: Relevance
“…31 However, numerous vascular diseases are characterized by the accumulation of smooth muscle cells in the intimal layer of blood vessels where they are surrounded by newly synthesized extracellular Wnt3a alters smooth muscle cell phenotype JM Carthy et al matrix. 3,4,32 These cells are generally thought of as dedifferentiated and synthetic, in that they display a loss of contractile differentiation, but an increased capacity to synthesize matrix proteins. 31 Although traditionally it has been thought that smooth muscle cells existed in either a synthetic or contractile state, it is now being recognized that there is considerable heterogeneity in smooth muscle cell populations and in some instances, contractile differentiation markers may be expressed simultaneously with matrix synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 However, numerous vascular diseases are characterized by the accumulation of smooth muscle cells in the intimal layer of blood vessels where they are surrounded by newly synthesized extracellular Wnt3a alters smooth muscle cell phenotype JM Carthy et al matrix. 3,4,32 These cells are generally thought of as dedifferentiated and synthetic, in that they display a loss of contractile differentiation, but an increased capacity to synthesize matrix proteins. 31 Although traditionally it has been thought that smooth muscle cells existed in either a synthetic or contractile state, it is now being recognized that there is considerable heterogeneity in smooth muscle cell populations and in some instances, contractile differentiation markers may be expressed simultaneously with matrix synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…28 It has previously been reported that connexin 43 expression is upregulated in smooth muscle cells in response to injury in rodent models and in early human atherosclerosis, situations in which elevated Wnt signaling has been reported 7,14 and in which increased extracellular matrix synthesis is well documented. 3,38 Reducing connexin 43 expression has been shown to inhibit lesion development in rodent models of atherosclerosis and acute vascular injury, [39][40][41] suggesting potential pro-atherogenic functions for gap junction communication. Our data suggest Wnt3a increases the expression of connexin 43 in vascular smooth muscle cells, and this increase in connexin 43 expression is associated with increased intercellular communication and matrix synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it would enable the physician to treat the population of patients (up to 30%) who actually develop a problem with stenosis or restenosis. Of particular interest from the perspective of this review, a consistent feature of acute intimal hyperplasia is the increased content of versican (Nikkari et al 1994, Finn et al 2002, Kenagy et al 2005, Chung et al 2002, Farb et al 2004. Therefore, understanding the mechanisms of intimal regression and the role of versican in this process is of great interest.…”
Section: Versican In Intimal Hyperplasiamentioning
confidence: 97%
“…Intimal atrophy occurs spontaneously in stented arteries after 6 months in humans (Asakura et al 1998) and 2 months in rats (Finn et al 2002, Langeveld et al 2004. At these late times during regression, the extracellular matrix (ECM) shows a relative loss of versican and a gain of collagen compared to earlier times (Chung et al 2002, Finn et al 2002, Langeveld et al 2004, Farb et al 2004. These data suggest that versican accumulates during neointimal progression and is lost during neointimal regression in the native artery.…”
Section: Versican Metabolism In Intimal Regressionmentioning
confidence: 99%
See 1 more Smart Citation